War, Peace and Love by Emmanuel Lévinas - Barszczak, Stanisław (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2012)
In a world in which everything is reduced “to the play of signs detached from what is signified,” Levinas asks a deceptively simple question: Whence, then, comes the urge to question injustice? By seeing the demand for justice for the other-the homeless, the destitute-as a return to morality, Levinas escapes the suspect finality of any ideology. Levinas’s question is one starting point for la Proximity. “If it is true that we are, through technology, moving closer and closer to one another,” writes some editors of the Levinas’s books, then “the importance of proximity and our response to it cannot be overstated.” For the author to this article, to which he can contribute something of significant value, the question of whether we may, ethically, appropriate the object of study for our own causes has become vital. Levinas asks us to see ourselves, our own reading, “in proximity” to what is not ourselves, not our understanding of the world. “Driven Back to the Text” demonstrates that what is at issue here is the Holocaust, and how it drives Levinas back to the Bible, the Kabbalah and the Talmud to fight against Hegelianism, totalitarianism and modern progressivist liberalism. This very return suggests a certain hermeneuticone that both brings out of the texts what the readers society needs to hear as well as one found in the texts; that is, it is an ethical hermeneutic and is part of the texts ethics. Beginning with a clear introduction to Levinas, the article argues that if, as is accepted, contemporary continental philosophy is heavily influenced by Levinas, and if Levinas is heavily influenced by the bible, then contemporary continental philosophy is at least to some extent influenced by christianism.
Keywords: Transcendence; Meaningful